EFFECT OF ENRICHMENT AND EMPOWERMENT ON COMPETENCY IN IMPROVING EMPLOYEE PERFORMANCE - Bina Muwadah Rohma; Mohammad Wasil (Jurnal Ekonomi, 2019)
This study aims to analyze the effect of Enrichment and Empowerment on improving employee performance in Bn'D Control System Surabaya. The sample used is 40 respondents with quantitative research methods with data analysis using Path Analysis. The company always wants employee performance to contribute well, so the company needs to implement employee enrichment and empowerment programs. The results of this study indicate that Empowerment has a more positive and significant effect on employee performance. Meanwhile, Enrichment and Competence in the Bn'D Control System affect but not significantly on employee performance.